Economic Dispatch of Electric Power in Microgrids using GAMS Software - Braz Pontes, Luiz Renato (2018)
Over time the electric market has been growing with the insertion of several sources, in addition to storage devices, given this panorama, the question arises of how to dispatch the energy generated to meet the demand in a more economical and efficient way. This work presents the implementation of a mathematical model of mixed integer nonlinear programming for the problem of Alternating Current Optimal Power Flow (ACOPF) using the GAMS software. In order to solve the problem of allocation and optimal operation of storage devices in microgrids, as well as the optimal cycle of loading and unloading of this devices in a way to minimize system operational costs. The model observes grid constraints, such as the voltage profile within permissible limits, as well as the intermittency of renewable sources based on wind and solar energy, represented by variable dispatches during the operation. To demonstrate the accuracy of the mathematical model developed and the efficiency of the solution techniques, a 5 bus test system